Physical inactivity interacts with an endothelial lipase polymorphism to modulate high density lipoprotein cholesterol in the GOLDN study - Smith, Caren E. (2009)
BACKGROUND: Plasma high density lipoprotein (HDL) cholesterol (HDL-C) concentration is highly heritable but is also modifiable by environmental factors including physical activity. HDL-C response to exercise varies among individuals, and this variability may be associated with genetic polymorphisms in the key regulators of HDL metabolism including endothelial lipase (LIPG). METHODS: We examined associations between variants LIPG T111I (rs2000813) and LIPG i24582 (rs6507931), HDL and television viewing/computer use (“screen time”) as a marker for physical inactivity in a population with high prevalence of metabolic syndrome. Subjects consisted of 539 White men and 584 women (mean ± S.D., 49 ± 16 years) participating in the GOLDN study. RESULTS: We did not observe an association with either LIPG SNP or HDL independently of screen time. In multi-adjusted linear regression models, HDL interacted significantly with screen time as a continuous variable in LIPG i24582 subjects with TT genotype (P < 0.05). By dichotomizing screen time into high and low levels, we found significant genotype-associated differences in HDL in women but not men. When screen time was ≥2.6 h/day, the concentrations of total HDL-C, large HDL, large low density lipoprotein (LDL) were lower, the concentration of small LDL was higher and HDL and LDL particle sizes were smaller in subjects with LIPG i24582 TT compared to CT and CC subjects (P < 0.05). CONCLUSIONS: We found a significant gene-physical inactivity interaction for HDL and some LDL measures for the LIPG i24582 polymorphism. Higher levels of physical activity may be protective for HDL-C concentrations and low activity detrimental in LIPG i24582 TT individuals, especially in women.